Acción extraordinaria de protección en el ecuador con efecto suspensivo en la sentencia según el artículo 437 de la constitución de la República del Ecuador. Estudio de casos en juzgados civiles del cantón Machala, provincia de El Oro – año 2013. - Orellana Espinoza, Juan Pablo (2015)
The present research work, we have taken into consideration by the conflict generated when framing the Special Protection Action. It is the case since the action arises not are asserting constitutional rights because the access demand to this action after a final judgment it is understood that it is to safeguard the constitutional rights of the party that has meaning affected but the reality is different, since at the time of accessing it and if accepted, the process that gave birth to the extraordinary action the process is sent directly to the Constitutional Court, leaving a copy in the court of origin and the Law on Jurisdictional Guarantees and Constitutional Control does not send well but indicates that from the first moment that it arises shall not stay on the main process, ie that while the process is in the Constitutional Court the initial process take its course Normal regardless of fault subsequently issued by the Constitutional Court born the problem on which we base this thesis, composed of five chapters. The first chapter focuses on the problem posed as such, its scope and theoretical study prior to analysis. The second chapter focuses on a strict, technical, theoretical, doctrinal and benchmark the different approaches of the unknown raised in this work study. The third chapter pays special attention to the methods and techniques required in order to investigate objectively and scientific criteria, the fourth chapter tests the professional skills of the proponents. And still necessary for an intervention proposal the fifth and final chapter of this research takes place, justifying their intervention and scope of it is made. Annexes and bibliography close this work to highlight the work done by the proponents cited in this paper.